To What Extent Can Body Politics be Used to Define Afghan Womens Sexuality as Locations of Power and Control under Taliban’s Rule? A Contemporary Foucauldian Interpretation of Femininity in Body Politics (Global Journal of Human-Social Science, 2023)
Central Asia Iran to the west and Pakistan to the east We are in Afghanistan and more specifically in a Taliban-controlled country The character of national politics and social connections in Taliban Afghanistan has been shaped by harsh gender policies and patriarchal restrictions The Taliban s leadership has exacerbated the country s weak social structure and lack of a centralised modern state resulting in a severe case of underdevelopment Goodson 2001 Statistics are instructive socio-economic issues such as unemployment and poverty account for 20 of national concerns while education account for 12 and finally a lack of essential amenities for 8 Bizhan 2013 In this difficult situation it is logical to wonder who are the most vulnerable members of this fractured society The focus turns to women Indeed women are the demographic segment paying the largest price for Afghan shortcomings in terms of Taliban decision-making Taliban s severe regulations on women who are denied of countless social opportunities under the Taliban patriarchal culture disguise Afghan underdevelopment resulting in detrimental inequalities inside the country Moghadam 2002
Keywords: women; foucault; body politics; afghanistan; development